An Analysis of Raman’s Psychopath Problem In “Raman Raghav 2.0” Film by Anurag Kashyap - Raja, S. R. Mohan; Tamilporai, Logranjan; Mouly, Chandra V (International Journal of Computer Sciences and Engineering, 2018)
The main aim of this research paper is to study the film “Raman Raghav 2.0”. In this research, the researcher has used the movie Raman Raghav 2.0 as the unit of analysis and has studied the characterization of the main character. This research is conducted by the application of psychological theories. The Abnormal Theory of Psychology is employed as the theoretical framework of the analysis. The individuals who are affected with Psychopathological Drawback are termed as “Psychopath”. Psychopaths are impulsive people who find it hard to control themselves. They never take time to weigh the merits of their action and they do not care about what they had done or what they are going to do in the future. Individuals affected with Psychopathological Drawback are easily triggered with trivial things. Psychopaths are people who get ignited with disappointment, failure, criticism and easily attack others just because of trivial things. Thus, to study these traits, a Descriptive Qualitative Structural Analysis Methodology has been adapted as this analysis clarifies the concerning intrinsic and extrinsic part of the film. According to the researcher, the intrinsic and extrinsic parts of the film are the dialogs used for communication and the scenarios used to highlight the main character’s activities that help us identify with the Psychopathological Drawback. Through observations of the scenes and the dialogues, the researcher can find that the filmmaker has evidently provided a unique characterization of the main character Raman, who exhibits Psychopathological Drawback. There are plenty of opportunity exist in the field of psychology and film’s impact. This research work can be extended to other similar films.